Healthy and Sustainable Diets in Bangladesh - Divya, Mehra; Tong, Junying; Dizon, Felipe; De Pee, Saskia (World Bank, Washington, DC, 2022)
An ideal food system is envisioned to provide healthy diets for people and be sustainable for the environment. Such a food system is required to deliver on these goals even as diets are increasingly and disproportionately comprised of high-fat and/or high-sugar foods vis-à-vis nutritious diets. The ideal “planetary health diet,” as defined in the EAT Lancet report for several countries, presents trade-offs when contextualized at the local level. Using Bangladesh as the case study, this paper examined the change in diets (between 2000 and 2016) and their greenhouse gas emissions over time and compared the nutritional value and environmental impact to two modeled diets: national food-based dietary guidelines and the planetary health diet/EAT Lancet diet. The analysis finds that despite a change of the diet toward the recommended diet, significant gaps remain from a nutritional perspective. Moreover, meeting the dietary guidelines would increase greenhouse gas emissions by at least 10 percent. Compared to the food-based dietary guidelines, the EAT Lancet diet requires dietary patterns to change even more significantly and would increase greenhouse gas emissions by 23 percent. The policy implications and options from the production and demand sides are complex and require assessing multiple trade-offs.